Incidence and risk factors associated with development of oxalipatin-induced acute peripheral neuropathy in colorectal cancer patients. (March 2023) - Ben Mahmoud, Imen Toukabri; Ben Said, Azza; Berguiga, Souad; Houij, Racha; Cherif, Ines; Hamdi, Adel; Ben Ayed, Wiem; Limayem, Imen
Introduction: Oxaliplatin utilized in colorectal neoplasms treatment could induce acute peripheral neuropathy (APN) which is a dreadful and frequent adverse event. The objective of this study is to estimate incidence of APN induced by oxaliplatin cumulative incidence in cancer patients colorectal and to describe the distribution of the APN incidence according to demographic and clinical characteristics, as well as according to oxaliplatin cumulative dose. Material and methods: This is a prospective descriptive study which took place from June to December 2018 at the Salah Azaiz Institute, Tunis. Demographic data, clinical data and data on oxaliplatin administration were collected from patient interview, medical files and pharmaceutical databases. Results: The APN (grade 1, grade 2 and grade 3) cumulative incidence during the period of six months of follow up was 86% (95% CI [0.7815–0.9132]). While 38.3% (95% CI [0.29–0.48]) of the patients had grade 2 or 3 neuropathy. The search for factors associated with the risk of grade 2 and 3 NAP revealed trend significant association with diabetes (adjusted RR = 5.7 (IC95% [0.9- 37.3]; p = 0.07). Moreover, there was significant association with oxaliplatin cumulative dose (≥421 mg/m2) to increase the risk of APN grade 2 and 3 (adjusted RR = 7.8; [2.7–22.7]; p = 0.0001). Furthermore, significant association with obesity to increase the risk of APN grade 2 and 3 (adjusted RR = 5.3 [1.1- 25.4]; p = 0.04) was found. Among the patients included, 31.1% experienced oxaliplatin dose reduction and in the majority of cases this reduction is due to neurotoxicity (90.9%). Conclusion: The high incidence of oxaliplatin-induced APN remains an embarrassing and handicapping side effect. Our study has shown that oxaliplatin cumulative dose (≥421 mg/m2), diabetes and obesity are risk factor for the development of grade 2 and 3 APN.